Correlation vitamin D deficiency with obesity and impaired glucose metabolism in women with polycystic ovary syndrome - Achmad Zulfa Juniarto; Siti Zahra Ni'mah; Ahmad Syauqy (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Vitamin D deficiency is a worldwide problem, particularly in Indonesia. Obesity and impaired glucose metabolism have an impact on vitamin D status in women with polycystic ovarium syndrome and are still controversial. This study aimed to examine vitamin D levels and the correlation between obesity and impaired glucose metabolism in PCOS patients. This research employed analytical observational techniques with a case-control approach with 40 women diagnosed with Rotterdam Criteria PCOS in Mother and Child Hospital Kasih Ibu Tegal during September-October 2023. This study used the Chemiluminescent Mikropartikel Immunoassay (CMIA) method to measure vitamin D levels in the laboratory. The statistical test utilized were Shapiro-Wilk, Paired T-Test and Mann Whitney and Chi Square. Results: There was no significant difference in the serum 25(OH)D levels between women with PCOS and controls (p>0,05; p=0,745). The group of patients with an obese waist circumference was 9.75 times more likely to develop PCOS than the group with a normal waist circumference (OR = 9,75; 95% CI = 1,16-82,11; p = 0,013). In conclusion, there was no substantial variation in vitamin D levels between PCOS and non-PCOS patients. Vitamin D deficiency correlates with obesity but does not correlate with impaired glucose metabolism.